The Influence of Cooperative Lending Sejahtera Bahari to Small and Medium Enterprise Development in Mamuju District, Indonesia - Nurhidayah, St.; Callo, Herman; Halim , Abdul (Manunggal Halim Jaya, 2024)
This research design is a quantitative study that examines the relationship between the effect of Bahari Prosperous Cooperative credit distribution and the development of small and medium enterprises (SMEs) in Mamuju Regency. The study employs a quantitative analysis method, utilizing numerical data collected from respondents' responses on a Likert scale ranging from 1 (lowest) to 5 (highest). A research questionnaire was distributed to 30 respondents using purposive and subjective sampling techniques. The research data was processed using multiple linear regression analysis with SPSS software version 24.0 to determine the influence of the independent variable on the dependent variable through a partial t-test. The analysis in this study follows a simple linear regression formula, where the independent variable (X) represents credit distribution, and the dependent variable (Y) represents business development. Hypothesis testing of the Sejahtera Bahari Cooperative credit distribution variable (X) yielded a significance value of 0.889, using a significance threshold of 0.05 (5%). Since the obtained significance value (0.889) is greater than 0.05, and the t-count (-0.140) is less than the t-table value (2.05183), it indicates that the distribution of Sejahtera Bahari Cooperative credit has no significant effect on the development of SMEs in Mamuju Regency. As a result, H₁ is rejected, and H₀ is accepted, meaning the hypothesis is not supported. Furthermore, the correlation between the distribution of Sejahtera Bahari Cooperative credit and the development of SMEs in Mamuju Regency is very weak, as indicated by a correlation coefficient of 0.026, which falls within the coefficient interval of 0.00 – 0.199.